Candida glabrata's recurrent infections: biofilm formation during Amphotericin B treatment. (August 2016) - Rodrigues, C.F.; Silva, S.; Azeredo, J.; Henriques, M.
Abstract: Candida species are responsible for recurrent human infections, mostly in immunocompromised patients, due to their high vulnerability. Candida glabrata has a major role in systemic candidiasis and Amphotericin B (AmB), a polyene only used in hospitals, is frequently used to treat this disease. Lately, however, clinical evidences of Candida recurrent infections during these treatments are being described, probably due to biofilm (re)formation during this therapy. Thus, this work aims at inferring if C. glabrata biofilms are still being formed during AmB treatment. For that, C. glabrata biofilms were formed in the presence of AmB and analysed by dry weight. Matrix composition was analysed quantifying carbohydrates and, specifically, β‐1, 3 glucans. Results demonstrated that, although in a lesser extent, C. glabrata is able to develop biofilms in the presence of AmB, with a thick extracellular matrix, with an increase on carbohydrates, especially β‐1, 3 glucans. Therefore, it is confirmed that complex biofilms of C. glabrata can be formed during an AmB treatment. Significance and Impact of the Study: This study shows new insights regarding recurrent candidiasis. The authors demonstrated that Amphotericin B did not totally prevent the development of biofilms during Candida glabrata 's infection treatment and that the change in the biofilm matrices may have a high responsibility for the fail in the treatment of systemic candidiasis. Abstract : Significance and Impact of the Study: This study shows new insights regarding recurrent candidiasis. The authors demonstrated that Amphotericin B did not totally prevent the development of biofilms during Candida glabrata 's infection treatment and that the change in the biofilm matrices may have a high responsibility for the fail in the treatment of systemic candidiasis.